1995
DOI: 10.1007/bf00168917
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pacemaker current by the bradycardic agent ZD 7288 is lost use-dependently in sheep cardiac Purkinje fibres

Abstract: The inhibition of the pacemaker current (if) in sheep cardiac Purkinje fibers by ZD 7288 [4-(N-ethyl-N-phenylamino)-1,2-dimethyl-6-(methylamino)pyrimidinium++ + chloride] is lost use-dependently. This disinhibition of if was investigated by using the two-microelectrode voltage-clamp technique. The pulse protocol consisted of a rest period (holding potential of about -50 mV, 1-10 micromol/l ZD 7288) followed by a train of test pulses (potential negative to -100 mV, stimulation frequency 0.05 Hz). At the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The most remarkable property of ZD7288 blockade of mHCN1 channels is its steep voltage dependence, corresponding to approximately four elementary charges moving through the entire transmembrane field. It has been previously demonstrated that the blocking effect of ZD7288 is relieved by hyperpolarization (BoSmith et al, 1993;Harris and Constanti, 1995;Gasparini and Di-Francesco, 1997) and that the voltage dependence of disinhibition was 4.8 mV/e-fold change (Berger et al, 1995). This slope value is equivalent to a z␦ of 5.3 (similar to z␦ Ϸ 4.2 measured here for mHCN1).…”
Section: Voltage Dependence Of Zd7288 Blocksupporting
confidence: 84%
“…The most remarkable property of ZD7288 blockade of mHCN1 channels is its steep voltage dependence, corresponding to approximately four elementary charges moving through the entire transmembrane field. It has been previously demonstrated that the blocking effect of ZD7288 is relieved by hyperpolarization (BoSmith et al, 1993;Harris and Constanti, 1995;Gasparini and Di-Francesco, 1997) and that the voltage dependence of disinhibition was 4.8 mV/e-fold change (Berger et al, 1995). This slope value is equivalent to a z␦ of 5.3 (similar to z␦ Ϸ 4.2 measured here for mHCN1).…”
Section: Voltage Dependence Of Zd7288 Blocksupporting
confidence: 84%
“…For GH 3 pituitary tumor cells it is known that membrane-bound estrogen receptors are removed by trypsin (Watson et al 1995). Furthermore, we have shown that drug-induced effects in sheep Purkinje fibres are manipulated severely by protease treatment (Berger et al 1995b).…”
Section: Discussionmentioning
confidence: 88%
“…At very positive potentials (>+40 mV), the rate of inactivation after FKBP12.6 expression was enhanced compared to the control values. I to is active during phase 1 of the cardiac action potential, and drug-induced reduction of I to is known to prolong action potential duration [2]. A more rapid inactivation (as observed after FKBP12.6 over-expression) might be expected to prolong the action potential duration, but this link has not been reported.…”
Section: Discussionmentioning
confidence: 99%